The synergistic antibacterial activity and mechanism of colistin-oxethazaine combination against gram-negative pathogens - Li, Jie; Han, Ning; Li, Yangyang; Zhao, Feifei; Xiong, Wenguang; Zeng, Zhenling (Frontiers in Pharmacology, 2024)
The rapid spread of bacteria with plasmid-mediated resistance to antibiotics poses a serious threat to public health. The search for potential compounds that can increase the antibacterial activity of existing antibiotics is a promising strategy for addressing this issue. Methods: Synergistic activity of the FDA-approved agent oxethazine combined with colistin was investigated in vitro using checkerboard assays and time-kill curves. The synergistic mechanisms of their combination of oxethazine and colistin was explored by fluorescent dye, scanning electron microscopy (SEM) and LC-MS/MS. The synergistic efficacy was evaluated in vivo by the Galleria mellonella and mouse sepsis models. Results: In this study, we found that oxethazine could effectively enhance the antibacterial activity of colistin against both mcr-positive andnegative pathogens, and mechanistic assays revealed that oxethazine could improve the ability of colistin to destruct bacterial outer membrane and cytoplasmic membrane permeability. In addition, their combination triggered the accumulation of reactive oxygen species (ROS), causing additional damage to the membrane structure resulting in cell death. Furthermore, oxethazine significantly enhanced the therapeutic efficacy of colistin in two animal models. Conclusion: These results suggested that oxethazine, as a promising antibiotic adjuvant, can effectively enhance colistin activity, providing a potential strategy for treating multidrug-resistant bacteria.